Factors Affecting the Accountability of Village Fund Management in Pineung Siribee - Sarah Nabila; Mandalena; Yusra; Ramadhani; Siti Zuhra (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the factors influencing the accountability of village fund management in Pineung Siribee Village, Samalanga District, Bireuen Regency. The problem addressed is the low level of accountability due to limited competence of village officials, weak community participation, and insufficient internal control systems. Data were collected from 36 respondents using questionnaires and analyzed with multiple linear regression through SPSS version 24. The results show that the competence of village officials, community participation, and internal control systems have a positive and significant effect on accountability, both partially and simultaneously. These findings conclude that strengthening competence, increasing participation, and reinforcing internal controls are crucial to improve accountability in village fund management.